An All‐Stretchable‐Component Sodium‐Ion Full Battery. Issue 23 (7th April 2017) - Li, Hongsen; Ding, Yu; Ha, Heonjoo; Shi, Ye; Peng, Lele; Zhang, Xiaogang; Ellison, Christopher J.; Yu, Guihua
Abstract : Stretchable energy‐storage devices receive considerable attention due to their promising applications in future wearable technologies. However, they currently suffer from many problems, including low utility of active materials, limited multidirectional stretchability, and poor stability under stretched conditions. In addition, most proposed designs use one or more rigid components that fail to meet the stretchability requirement for the entire device. Here, an all‐stretchable‐component sodium‐ion full battery based on graphene‐modified poly(dimethylsiloxane) sponge electrodes and an elastic gel membrane is developed for the first time. The battery exhibits reasonable electrochemical performance and robust mechanical deformability; its electrochemical characteristics can be well‐maintained under many different stretched conditions and after hundreds of stretching–release cycles. This novel design integrating all stretchable components provides a pathway toward the next generation of wearable energy devices in modern electronics. Abstract : An all‐stretchable‐component sodium‐ion full battery is fabricated using graphene‐modified PDMS sponge electrodes. This novel designed stretchable battery shows outstanding electrochemical performance and robust mechanical deformability. It is expected to be suitable for application in various stretchable electronic devices.